2012
DOI: 10.1073/pnas.1113811109
|View full text |Cite
|
Sign up to set email alerts
|

Loss of insulin-induced activation of TRPM6 magnesium channels results in impaired glucose tolerance during pregnancy

Abstract: Hypomagnesemia affects insulin resistance and is a risk factor for diabetes mellitus type 2 (DM2) and gestational diabetes mellitus (GDM). Two single nucleotide polymorphisms (SNPs) in the epithelial magnesium channel TRPM6 (V 1393 I, K 1584 E) were predicted to confer susceptibility for DM2. Here, we show using patch clamp analysis and total internal reflection fluorescence microscopy, that insulin stimulates TRPM6 activity via a phosphoinositide 3-kinase and Rac1-mediated elevation of cell surface expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 36 publications
(52 reference statements)
4
138
1
1
Order By: Relevance
“…Interestingly, common SNPs in the TRPM6 gene are associated with an increased risk of developing diabetes mellitus type 2 (489). TRPM6 cannot be activated by insulin when these SNPs are present (361). These results suggest that Mg 2ϩ levels may influence the onset and development of diabetes mellitus type 2.…”
Section: Diabetesmentioning
confidence: 82%
See 1 more Smart Citation
“…Interestingly, common SNPs in the TRPM6 gene are associated with an increased risk of developing diabetes mellitus type 2 (489). TRPM6 cannot be activated by insulin when these SNPs are present (361). These results suggest that Mg 2ϩ levels may influence the onset and development of diabetes mellitus type 2.…”
Section: Diabetesmentioning
confidence: 82%
“…Insulin may directly affect TRPM6 activity through cylin-dependent kinase 5 (cdk5)-dependent phosphorylation of the channel. Patients with reduced EGFR or insulin receptor (IR) activity are therefore more susceptible to hypomagnesemia (361,459). Additionally, estrogens increase TRPM6 mRNA expression (196).…”
Section: Distal Convoluted Tubulementioning
confidence: 99%
“…Two SNPs in TRPM6 (p.Val1393Ile [rs3750425] and p.Lys1584Glu [rs2274924]) are associated with increased susceptibility for gestational diabetes mellitus (71). Patch clamp analysis showed that these mutations render the channel insensitive to insulin stimulation (94). Follow-up studies could not confirm associations between serum Mg 2+ values and these two SNPs (69,95).…”
Section: Trpm6mentioning
confidence: 88%
“…In contrast, insulin resistance has been proposed to explain the reduced TRPM6 activity and hypomagnesemia in T2DM (94). Until now, it has been widely accepted that Na + and Mg 2+ transport in the DCT go hand in hand, since reduced NCC activity causes hypomagnesemia as shown in patients with Gitelman syndrome and in users of thiazide diuretics (105,106 Reports on diabetic retinopathy suggest that insulin regulates the potassium channel Kir4.1 in the retina (107,108).…”
Section: Diabetes-dct Paradoxmentioning
confidence: 99%
“…Insulin was reported to enhance surface expression of TRPM6 in human b cells. Two TRPM6 variants (V1393I and K1584E) were recently described in women with gestational DM (Nair et al, 2012).…”
Section: +mentioning
confidence: 99%